REPORT OF EXAMINATION OF ACCOUNTS. (The Accounting Review, 1956)
The article presents a report on examination of accounts for the year 1955 addressed to the executive committee of the American Accounting Association. It states that the financial position of the association had been examined in accordance with generally accepted auditing standards which included tests of the accounting records and other auditing procedures considered necessary. Exhibit A of the article presents the statement of financial position as related to assets, liabilities and net worth against general funds. Exhibit B, presents the statement of income against general fund as related to income, expenses and net income of the association during the year 1955. The statement of income against life membership fund in relation to income, expense and net loss of the association has been represented in Exhibit C, while an analysis of changes in net worth and net income of the association against general fund has been illustrated in Exhibit D. The article also provides notes to the financial statements, stating that, the negative cash amount in the life membership fund is not a bank overdraft among others.